Coastal Cities: Challenges and Opportunities for Rio’s Coastal Slums, with a Focus on Maré - Nascimento, Thayna Cristina Gomes do; Cardozo , Dyanna de Abreu; Silva, Amanda Alves da; Carriello, Felix (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – Faced with rising sea levels, this study aims to analyze urban resilience in the context of Rio de Janeiro’s favelas, focusing on the Complexo da Maré. Methodology – The research uses a bibliographic review and georeferenced data analysis to identify vulnerabilities and potential solutions. Originality/Relevance – The importance of this work lies in addressing gaps in understanding how marginalized coastal communities, such as Rio’s favelas, can adapt to the impacts of climate change. These areas, often relegated to the margins of society, house a significant portion of the population and require greater attention due to their socioeconomic and environmental vulnerabilities. Results – The study reveals that rising sea levels threaten the quality of life in the Complexo da Maré, highlighting the need for nature-based solutions, community participation, and sustainable infrastructure to mitigate socio-environmental vulnerabilities. Theoretical/Methodological Contributions – This study contributes to the theoretical understanding of urban resilience in marginalized coastal communities by highlighting the interplay between climate change impacts and socio-environmental vulnerabilities. Methodologically, it integrates bibliographic review and georeferenced data analysis to propose nature-based, community-driven, and infrastructural solutions for adaptation and mitigation in urban coastal areas. Social and Environmental Contributions – The proposed strategies can reduce vulnerabilities and improve the quality of life for residents of coastal favelas.